2019
DOI: 10.1186/s13046-019-1036-z
|View full text |Cite|
|
Sign up to set email alerts
|

Melatonin synergizes BRAF-targeting agent vemurafenib in melanoma treatment by inhibiting iNOS/hTERT signaling and cancer-stem cell traits

Abstract: Background: As the selective inhibitor of BRAF kinase, vemurafenib exhibits effective antitumor activities in patients with V600 BRAF mutant melanomas. However, acquired drug resistance invariably develops after its initial treatment.Methods: Immunohistochemical staining was performed to detect the expression of iNOS and hTERT, p-p65, Epcam, CD44, PCNA in mice with melanoma xenografts. The proliferation and migration of melanoma cells were detected by MTT, tumorsphere culture, cell cycle, cell apoptosis, AO/EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…In ammatory signalling pathways are closely related to the pathological changes of various chronic diseases in vivo [16,17]. The proin ammatory cytokines produced by the activation of signalling pathways promote the activation of T cells, which plays an important role in the progression of various autoimmune diseases, including pSS [18,19]. Conversely, in ammatory mediators also interfere with the expression of clock genes [20], but the relevant mechanisms involved are complex and have not been fully elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ammatory signalling pathways are closely related to the pathological changes of various chronic diseases in vivo [16,17]. The proin ammatory cytokines produced by the activation of signalling pathways promote the activation of T cells, which plays an important role in the progression of various autoimmune diseases, including pSS [18,19]. Conversely, in ammatory mediators also interfere with the expression of clock genes [20], but the relevant mechanisms involved are complex and have not been fully elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in our study, the disordered expression of clock genes observed in pSS patients and animals may be the cause of pSS, or excessive in ammatory responses may disturb the normal expression of biological clock genes. Melatonin can inhibit a variety of important in ammation-related pathways and molecules and may reduce in ammation by blocking these in ammatory signalling pathways, which are closely related to the progression of pSS [9,19,[28][29][30]. Moreover, as a broad antioxidant, melatonin can effectively reduce tissue damage during chronic in ammation [8,9,31].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence has demonstrated that melatonin has anti‐tumour effect in various cancers, such as melanoma, breast cancer, lung carcinoma and thyroid cancer 24‐27 . Melatonin has been shown to be an effective combination therapy for cancers by improving the curative effect of conventional anticancer drugs, reducing their side effects and overcoming their resistance to chemotherapy 28,29 . However, the combination of melatonin and BRAF‐targeting agent dabrafenib for the treatment of anaplastic thyroid cancer has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Melatonin has been shown to be an effective combination therapy for cancers by improving the curative effect of conventional anticancer drugs, reducing their side effects and overcoming their resistance to chemotherapy. 28,29 However, the combination of melatonin and BRAF-targeting agent dabrafenib for the treatment of anaplastic thyroid cancer has not been reported.…”
mentioning
confidence: 99%
“…By means of modulation of OXPHOS, melatonin may finally enhance the mitochondria-mediated proapoptotic effect of BRAF/MEK inhibitors. [39][40][41] Moreover, altered melanin synthesis induced by melatonin may lead to changes in cell plasticity and thus invasiveness.…”
mentioning
confidence: 99%